2017
DOI: 10.1007/s00425-017-2657-0
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing of representational difference analysis products for identification of genes involved in diosgenin biosynthesis in fenugreek (Trigonella foenum-graecum)

Abstract: Main conclusion Representational difference analysis of cDNA was performed and differential products were sequenced and annotated. Candidate genes involved in biosynthesis of diosgenin in fenugreek were identified. Detailed mechanism of diosgenin synthesis was proposed.Fenugreek (Trigonella foenum-graecum L.) is a valuable medicinal and crop plant. It belongs to Fabaceae family and has a unique potential to synthesize valuable steroidal saponins, e.g., diosgenin. Elicitation (methyl jasmonate) and precursor fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 50 publications
2
17
0
Order By: Relevance
“…However, based on the bioinformatics analysis here, we proposed the same set of enzymes probably occurring in the cholesterol and phytosterol pathways in D. zingiberensis . A similar case was also previously suggested for another diosgenin-producing plant Trigonella foenum-graecum [ 17 ]. The unigenes encoding all the known pathway enzymes from IPP to cholesterol were discovered in the D. zingiberensis transcriptome ( Table 2 ), including two for GPPS, one for FPPS, one for SS, one for SE, one for CAS, two for SSR, one for SMO1, one for CYP51, one for C14-R, one for 8,7 SI, one for SMO2, one for C5-SD, and one for 7-DR.…”
Section: Resultssupporting
confidence: 80%
“…However, based on the bioinformatics analysis here, we proposed the same set of enzymes probably occurring in the cholesterol and phytosterol pathways in D. zingiberensis . A similar case was also previously suggested for another diosgenin-producing plant Trigonella foenum-graecum [ 17 ]. The unigenes encoding all the known pathway enzymes from IPP to cholesterol were discovered in the D. zingiberensis transcriptome ( Table 2 ), including two for GPPS, one for FPPS, one for SS, one for SE, one for CAS, two for SSR, one for SMO1, one for CYP51, one for C14-R, one for 8,7 SI, one for SMO2, one for C5-SD, and one for 7-DR.…”
Section: Resultssupporting
confidence: 80%
“…MeJA mainly act as elicitor in plant defense under biotic and abiotic stresses. Majority of the transcripts involved in diosgenin biosynthesis including various P450 was found to be upregulated after MeJA treatment (Ciura et al 2017) that further confirms the involvement of MeJA in the upregulation of secondary biosynthetic pathway related gene.…”
Section: Trigonella Foenum-graecumsupporting
confidence: 52%
“…Cholesterol is formed from lanosterol and catalysed by the cytochrome P450 system. Several other routes of synthesis have been identified, such as from squalene-2,3-oxide in two ways: From cycloartenol through the formation of sitosterol [ 51 ] and from lanosterol via cholesterol [ 52 ]. Several studies have demonstrated the diverse biological activities of diosgenin, such as hypolipidemic, anti-inflammatory, anti-proliferative, hypoglycemic activity, and as a potent anti-oxidant [ 44 ].…”
Section: Introductionmentioning
confidence: 99%